Application of hybrid real-time power system simulator for research and setting a momentary and sustained fast turbine valving control; IET Generation, Transmission & Distribution; Vol. 12, iss. 1 - Andreev M. V. Mikhail Vladimirovich; Borovikov Y. S. Yuri Sergeevich; Gusev A. S. Alexander Sergeevich; Sulaymanov A. O. Almaz Omurzakovich; Ruban N. Yu. Nikolay Yurievich; Suvorov A. A. Aleksey Aleksandrovich; Ufa R. A. Ruslan Alexandrovich; Bems J. Julius; Kralik T. Tomas (2018, 2018)
Title screen